The prevalence of pseudorabies virus in China from 2010 to 2024: a systematic review and meta-analysis - Weihao Gao; Min Zhang; Zhenbang Zhu (BMC Veterinary Research)
Abstract Background Pseudorabies virus (PRV) is one of the most important swine pathogens, causing annual global economic losses of billions of dollars to the pig industry. Due to PRV’s high resistance, persistent latency, and complex transmission dynamics, once infection is established in pig farms, substantial difficulties in eradication are presented. Therefore, it is important to understand the prevalence, spatial distribution and temporal trends of PRV in swine herds. Method We performed a systematic review and meta-analysis to evaluate the epidemiological characteristics of PRV in the swine herds across China. A total of 70 eligible studies were systematically retrieved from five comprehensive databases. Results The results revealed an overall pooled prevalence of PRV in China at 21.5% during the period from 2010 to 2024. There was a higher prevalence rate of 26.1% between 2010 and 2016 compared to subsequent years. Moreover, the prevalence of PRV in Inner Mongolia was 47.4%, exceeding other provinces. Additionally, serological assays yielded the highest detection rate at 29.1%. Furthermore, sows exhibited a higher susceptibility to PRV infection than boars. The results did not reveal significant variations in PRV infection rates based on gender or age. Conclusion Our nationwide surveillance revealed persistent PRV circulation in China, with particularly high prevalence in certain regions. This necessitates targeted and differentiated control strategies prioritizing high-endemic areas, where intensified measures could maximize containment efficacy while optimizing resource allocation.